Illuminating the Chaos and Obscurity: Polyphony in Fyodor Dostoevsky and Elena Ferrante - Sarah Hudspith; Olivia Santovetti (Modern Languages Open)
This article brings into dialogue the nineteenth-century Russian author Fyodor Dostoevsky and the twenty-first-century Italian novelist Elena Ferrante. As well as sharing thematic similarities in their fiction, such as poverty, violence and social disorder, Dostoevsky and Ferrante both place significant emphasis on the role of the writer, through their fictional narrators and in autobiographical writings. Drawing on the theories of Mikhail Bakhtin, we analyse the way in which Dostoevsky and Ferrante use polyphonic techniques to address their shared preoccupation with the artifice of narrative and their concern for authentic writing. We ask the following questions: How do Dostoevsky and Ferrante approach the paradox inherent in the creation of a narrative—an artificial construct—for the purpose of communicating a truth? What kind of writing do they consider authentic, and what is the nature of the human experience that authentic writing should expose? Given that Ferrante’s novels prioritise female protagonists, how does her use of polyphony compare to that of Dostoevsky, a writer who has at times been criticised for his portrayal of women and for the violence enacted against them in his fiction? Beginning with examples drawn from across the oeuvre of both authors, our analysis will culminate in a parallel reading of Dostoevsky’s The Adolescent and Ferrante’s latest novel The Lying Life of Adults.